Digital Design of Audio Signal Processing Using Time Delay - Perez, Mauricio; de Souza, Rodolfo Coelho; Faria, Regis Rossi Alves (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação Musical, 2019)
This poster describes the design in PureData of some audio signals processes in real time like delay, echo, reverb, chorus, flanger e phaser. We analyze the technical characteristics of each process and the psychoacoustic effects produced by them in human perception and audio applications. A deeper comprehension of the consequences of sound processes based on delay lines helps the decision-making in professional audio applications such as the audio recording, mixing, besides music composition that employs sound effects in preprocessed or real-time.